2022
DOI: 10.1051/0004-6361/202243171
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of polycyclic aromatic hydrocarbon ionization to neutral gas heating in galaxies: model versus observations

Abstract: The ionization of large carbonaceous molecules, i.e., polycyclic aromatic hydocarbons (PAHs), by ultraviolet (UV) photons from massive stars is expected to account for a large fraction of the heating of neutral gas in galaxies. Evaluation of this proposal, however, has been limited by our ability to directly compare observational diagnostics to the results of a molecular model describing PAH ionization. The objective of this article is to take advantage of the most recent values of molecular parameters derived… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Bakes & Tielens (1994) proposed theoretical models to estimate the contribution of nanograins and PAHs to the heating of interstellar gases depending on their sizes, typically up to 100 nm. Berné et al (2022) used a recent model considering new data from laboratory measurements on PAHs, and comparison of the model results with observational diagnostics yielded good agreement over a wide range of radiation fields, concluding that PAH ionization is the main source of neutral gas heating in regions where they are present abundantly and subjected to VUV photons, such as near starforming regions.…”
Section: Contribution Of Photoelectrons To the Gas Heating Of The Ismmentioning
confidence: 93%
See 1 more Smart Citation
“…Bakes & Tielens (1994) proposed theoretical models to estimate the contribution of nanograins and PAHs to the heating of interstellar gases depending on their sizes, typically up to 100 nm. Berné et al (2022) used a recent model considering new data from laboratory measurements on PAHs, and comparison of the model results with observational diagnostics yielded good agreement over a wide range of radiation fields, concluding that PAH ionization is the main source of neutral gas heating in regions where they are present abundantly and subjected to VUV photons, such as near starforming regions.…”
Section: Contribution Of Photoelectrons To the Gas Heating Of The Ismmentioning
confidence: 93%
“…It is noteworthy to mention that the present 2D matrix can be exploited to obtain the KE of the photoelectrons emitted from PAHs due to any incoming ISRF and, in turn, can be used to estimate the heating effect in the ISM. So far, the majority of studies on the heating of gases have been based on theoretical predictions, and such experimental measurements can serve as important input for models like that of Berné et al (2022), providing accurate information for the contribution of PAHs in maintaining the temperature balance in the ISM.…”
Section: Contribution Of Photoelectrons To the Gas Heating Of The Ismmentioning
confidence: 99%
“…The PAH-VUV interaction is a crucial process that partially governs the composition of the PAH population in space and thus the ensuing chemistry. Furthermore, the ionization of PAHs by VUV photons from massive stars is expected to account for a large fraction of the heating of neutral gas in galaxies and thus laboratory data on PAHs and any of their derivatives that are abundant in space are essential to test photoelectric heating models against observational diagnostics (Berné et al 2022). The substitution of PAHs by a CN functional group does not significantly alter the photoionization yield, considering that for similar and larger sizes, the bare radical cation PAHs presented photoionization yields ranging from 0.2 to 0.5 at 13.6 eV (Zhen et al 2016).…”
Section: Astrophysical Implications and Conclusionmentioning
confidence: 99%
“…PAHs, and hence helicenes, are strong UV-absorbers thus causing the heating of gas in the ISM, especially via their photoemission 20 . It has been suggested that through analysis of the relative intensities of specific mid-IR spectral features, it becomes feasible to trace the ionisation state of PAHs and thereby explore their radiative environment 9 .…”
Section: Introductionmentioning
confidence: 99%